2020
DOI: 10.5511/plantbiotechnology.19.1212b
|View full text |Cite
|
Sign up to set email alerts
|

A novel FLOURY ENDOSPERM2 (FLO2)-interacting protein, is involved in maintaining fertility and seed quality in rice

Abstract: Crop plants accumulate a large amount of storage starch and storage proteins in the endosperm. Genes involved in the biosynthesis of these substances work in concert during development of the rice endosperm. The rice flo2 mutant produces aberrant seeds with reduced grain quality. FLOURRY ENDOSPERM 2 (FLO2), the causative gene of the flo2 mutant, is considered to be a regulatory protein that controls the biosynthesis of seed storage substances. FLO2 contains tetratricopeptide repeat (TPR) motifs that may mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…FLO2 overexpression enhances the expression of starch enzyme (AGPL1, AGPL4 and GBSSI) and SSP genes (such as GluA1, glutelin A1, and 11Sglobulin) genes, the consequence of which was increased amylose content, grain weight and grain size, suggesting that it plays a pivotal regulatory role in rice yield and starch quality. FLOC1, an interactor of FLO2, also participates in the control of seed quality during grain filling (Suzuki et al, 2020). Liu et al (2023b) recently characterized an "Oat-like rice" mutant with poor grain quality, including abnormal morphology, chalky endosperm, loose arrangement of starch granules, higher GPC and lower starch content.…”
Section: Ricementioning
confidence: 99%
See 1 more Smart Citation
“…FLO2 overexpression enhances the expression of starch enzyme (AGPL1, AGPL4 and GBSSI) and SSP genes (such as GluA1, glutelin A1, and 11Sglobulin) genes, the consequence of which was increased amylose content, grain weight and grain size, suggesting that it plays a pivotal regulatory role in rice yield and starch quality. FLOC1, an interactor of FLO2, also participates in the control of seed quality during grain filling (Suzuki et al, 2020). Liu et al (2023b) recently characterized an "Oat-like rice" mutant with poor grain quality, including abnormal morphology, chalky endosperm, loose arrangement of starch granules, higher GPC and lower starch content.…”
Section: Ricementioning
confidence: 99%
“…FLO2 overexpression enhances the expression of starch enzyme ( AGPL1 , AGPL4 and GBSSI ) and SSP genes (such as GluA1, glutelin A1 , and 11S‐globulin ) genes, the consequence of which was increased amylose content, grain weight and grain size, suggesting that it plays a pivotal regulatory role in rice yield and starch quality. FLOC1, an interactor of FLO2, also participates in the control of seed quality during grain filling (Suzuki et al, 2020).…”
Section: Integrating Regulators Orchestrating Ssp and Starch Accumula...mentioning
confidence: 99%
“…One basic helix–loop–helix (bHLH) protein may interact with FLO2 to modulate the expression of starch biosynthesis-associated nuclear genes (SBANGs) [ 75 ]. Subsequently, the FLO2-interacting cupin domain protein 1 (FLOC1) was reported to interact with the TPR motif of FLO2 to maintain fertility and seed quality in rice [ 77 ], even though they are supposed to have different functions.…”
Section: Other Regulators Directly Affecting Starch Biosynthesismentioning
confidence: 99%
“…FLOURY ENDOSPERM 2 ( FLO2 ), a member of a conserved gene family in plants, encodes a tetratricopeptide repeat domain (TPR)-containing protein located in the nucleus ( She et al., 2010 ; Wu et al., 2015 ; Kolli et al., 2019 ; Suzuki et al., 2020 ). It has been reported that FLOURY ENDOSPERM 2 could not only modulate the expression of starch synthesis-related genes including OsAGPL2, OsAGPS2b, OsGBSSI, OsBEI, OsBEIIb, OsISA1 and OsPUL , but also directly impact on the amylose biosynthesis by manipulating the splicing efficiency of Wx pre-mRNA ( Wu et al., 2015 ; Cai et al., 2022 ; Feng et al., 2022 ; Sreenivasulu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that flo2 , the loss-of-function mutant of FLOURY ENDOSPERM 2 , produced two distinct phenotypes, one with white and floury endosperm, and the other with dull grain ( She et al., 2010 ; Hunt et al., 2013 ; Boehlein et al., 2018 ). In the former, starch granules were small, spherical and loosely packed with large air space ( Malinova et al., 2017 ; Jiang et al., 2018 ; Suzuki et al., 2020 ). The FLOURY ENDOSPERM 2 also affected grain size as demonstrated by both overexpression and null mutation approaches ( She et al., 2010 ; Zhang et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%